MALIGNANT DUODENOCOLIC FISTULA- CASE REPORT OF RARE COMPLICATION OF COLONIC CANCER TREATED BY MULTIVISCERAL RESECTION - Kadri, Edzevit; Nedelkovski, Dane; Lazova, Evgenija; Panikj, Katarina (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Duodenocolic fistulas created by invasive cancer of the colon are rare complications. They are presented with serious electrolytic and nutritional disturbances due to vomiting, diarrhoea, abdominal pain, GI bleeding, and weight loss.  Case report: In this paper we present young male patient with malignant duodenocolic fistula between ascendant colon and D2 portion of duodenum and pancreatic head, treated with right hemicolectomy and pancreaticoduoedenectomy. Postoperative histopathology confirmed poorly differentiated colonic adenocarcinoma without spreading to lymph nodes and major vessels. Patient is still alive after three years of the operation which led as to conclusion that this type of radical operation may represent one of the best treatments for this rare complication, provides good quality of life and is prognostically justifiable. Keywords: malignant duodenocolic fistula, advanced colorectal carcinoma (CRC), right hemicolectomy, pancreaticoduoedenectomy.